Strengthening Islamic Education Quality: A Conceptual Analysis of Evaluation and Monitoring in Educational Planning - Melyna Wijaya Putri; Idham Kholid; Koderi (Journal of Educational Management Research, 2026)
This study aims to analyze the role of evaluation and monitoring as strategic components in strengthening Islamic education quality through educational planning. This research employed a qualitative approach using library research methods by examining relevant academic literature, including journal articles and scholarly documents related to evaluation, monitoring, quality management, and Islamic education planning. The collected data were analyzed through data condensation, data display, verification, and conceptual synthesis to identify relationships among the main themes of the study. The findings reveal that evaluation and monitoring function as interconnected mechanisms that support continuous quality improvement in Islamic education. Evaluation provides evidence for assessing curriculum implementation, learning effectiveness, and institutional performance, while monitoring ensures consistency between educational planning, implementation, and improvement actions. The study also highlights that effective follow-up of evaluation and monitoring results is essential for developing sustainable quality assurance systems. This research contributes conceptually by integrating evaluation and monitoring into a comprehensive framework for Islamic education quality management. The implications of this study suggest that educational institutions should develop systematic, participatory, and continuous evaluation and monitoring strategies to enhance educational effectiveness and institutional quality.